Intrathecal melatonin increases the mechanical nociceptive threshold in the rat - Onal, Selami Ates; Inalkac, Suheyla; Kutlu, Selim; Kelestimur, Haluk (Turkish Society of Algology, 2004)
The aim of this investigation was to determine whether intrathecal (i.t.) administration of monodose melatonin provides an increase in mechanical nodceptive threshold in the rat. Twenty-four male Wistar rats were randomly assigned to four groups. Each animal was anesthetized, and a catheter was placed intrathecally via the cisterna magna. The study groups were: untreated controls (n=6); melatonin only (MEL, n=6); melatonin + luzindole (MEL+LZN, n=6); and melatonin + naloxone (MEL+NLX, n=6). Measurements of mechanical nociceptive threshold were made using an electronic algometer. Each animal was tested prior to injection and at 10, 20, 30 and 40 min after injection. In the MEL group, the mean nociceptive thresholds at all post-injection time points were significantly higher than the baseline value (p<0.05 for all). In the control and MEL+LZN groups, none of the four mean nociceptive thresholds recorded after i.t. injection was significantly different from the baseline value (p>0.05 for all). In the MEL+NLX group, the mean nociceptive thresholds at 20, 30 and 40 min post-injection were all significantly lower than the baseline value (p<0.05 for all). Comparison among the group nociceptive thresholds at baseline revealed no significant differences, and the same was true at 10 min after i.t. injection. At the 20, 30 and 40 min stages, the threshold in the MEL group was significantly higher than the threshold in the control group. The results indicate that i.t. injection of melatonin produces a time-dependent increase in mechanical nociceptive threshold in the rat and that the mechanism that underlies these effects involves both melatonin and opioid receptors.
Keywords: Intrathecal; Luzindole; Mechanical nociceptive threshold; Melatonin; Naloxone